2012
DOI: 10.1007/s12311-012-0388-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Atrophy in Patients with Subcortical-Type Vascular Cognitive Impairment

Abstract: Recent studies suggest that the role of the cerebellum extends into cognitive regulation and that subcortical vascular dementia (SVaD) can result in cerebellar atrophy. However, there has been no evaluation of the cerebellar volume in the preclinical stage of SVaD. We aimed to compare cerebellar volume among patients with amnestic mild cognitive impairment (aMCI) and subcortical vascular mild cognitive impairment (svMCI) and evaluate which factors could have contributed to the cerebellar volume. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…We aligned FDG-PET images to the corresponding structural MRI using a rigid body transformation, segmented the cerebellum [58] where glucose utilization is relatively preserved [59], and extracted the distribution volume ratio (DVR) image for intensity normalization. The three partial volume estimation maps of GM, WM and CSF indicating the portion of tissues within each voxel were calculated from MRI scans, and a weighted partial volume estimation map (wPVE) was calculated by the weighted sum of three partial volume estimation maps under the assumption that CSF is a non-uptake region and WM uptake is approximately one fourth that of GM [60].…”
Section: Methodsmentioning
confidence: 99%
“…We aligned FDG-PET images to the corresponding structural MRI using a rigid body transformation, segmented the cerebellum [58] where glucose utilization is relatively preserved [59], and extracted the distribution volume ratio (DVR) image for intensity normalization. The three partial volume estimation maps of GM, WM and CSF indicating the portion of tissues within each voxel were calculated from MRI scans, and a weighted partial volume estimation map (wPVE) was calculated by the weighted sum of three partial volume estimation maps under the assumption that CSF is a non-uptake region and WM uptake is approximately one fourth that of GM [60].…”
Section: Methodsmentioning
confidence: 99%
“…Cerebellar changes can occur in several types of dementia [65, 79ā€“82]. Generally, these findings are organized in neuroimaging secondarily, on the other hand, some cerebellar diseases may also present with dementia.…”
Section: Section 6: Radiological Biomarkers Of Cerebellar Alteration mentioning
confidence: 99%
“…In vascular dementia, cerebellar changes are diverse and brain atrophy can occur directly by vascular lesion in the cerebellum or secondary to cerebrum atrophy [89]. Studies have already found the fact that after stroke, the cerebellum suffered from reduction in metabolism and blood flow in the cerebellar hemisphere contralateral to a destructive cerebral lesion [79, 90]. But there is a particular change in subcortical vascular dementia that present with cerebellar volume reduction, and the number of subcortical lacunes correlates with cerebellar atrophy [91].…”
Section: Section 6: Radiological Biomarkers Of Cerebellar Alteration mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with svMCI have been shown to exhibit cognitive impairments in executive, language, visuospatial, and memory functions (Seo et al, 2009, 2010) and have been associated with structural and functional alterations in widespread regions (Seo et al, 2010; Yi et al, 2012, 2015; Yoon et al, 2013; Kim et al, 2014), while these functions are further impaired in cases of SVaD (Kim et al, 2014). In svMCI patients, subcortical areas, such as the basal ganglia and thalamus, are more prominently involved than the frontal region.…”
Section: Introductionmentioning
confidence: 99%